Enhancement of the efficiency of heat removal from powerful electronic devices through thermal interfaces based on aluminum nitride films - Rudenko, E.M.; Sorokin, V. M.; Korotash, I.V.; Polotsky, D.Yu.; Krakovny, A.O.; Suvorov, O.Yu.; Belogolovskii M.О.; Pekur, D.V. (Reports of the National Academy of Sciences of Ukraine, 2018)
The efficiency of aluminum nitride films as thermal interfaces has been studied. It is shown that such films obtained in a hybrid helicon-arc ion-plasma reactor significantly improve the heat removal from the crystals of electronic devices, in particular, from powerful LEDs or LED assemblies, and thus noteworthy increase their luminosity, reliability, and durability.